The Application of Satellite Imagery in Support of Nautical Charting; Past Experience and Future Possibilites. A Practical View - Craig, J. M. (The International Hydrographic Review, 2015)
This paper sets out to give a practical overview of how satellite imagery has been used to date in the UKHO and its likely future use in support of nautical charting. It is concerned only with commercially based digital systems. Systems designed primarily for defence purposes are not included. It should be noted that the views expressed herein are the result of the author’s own experience and do not necessarily represent the current official policies of the UKHO.